Functional dissection of inherited non-coding variation influencing multiple myeloma risk - Ajore, Ram; Niroula, Abhishek; Pertesi, Maroulio; Cafaro, Caterina; Thodberg, Malte; Went, Molly; Bao, Erik L.; Duran-Lozano, Laura; Lopez de Lapuente Portilla, Aitzkoa; Olafsdottir, Thorunn; Ugidos-Damboriena, Nerea; Magnusson, Olafur; et al. (Nature Communications, 2022)
Thousands of non-coding variants have been associated with increased risk of human diseases, yet the causal variants and their mechanisms-of-action remain obscure. In an integrative study combining massively parallel reporter assays (MPRA), expression analyses (eQTL, meQTL, PCHiC) and chromatin accessibility analyses in primary cells (caQTL), we investigate 1,039 variants associated with multiple myeloma (MM). We demonstrate that MM susceptibility is mediated by gene-regulatory changes in plasma cells and B-cells, and identify putative causal variants at six risk loci (SMARCD3, WAC, ELL2, CDCA7L, CEP120, and PREX1). Notably, three of these variants co-localize with significant plasma cell caQTLs, signaling the presence of causal activity at these precise genomic positions in an endogenous chromosomal context in vivo. Our results provide a systematic functional dissection of risk loci for a hematologic malignancy.
Gesehen am 19.03.2024